Evaluation of a prototype of an artisanal incubator for quail eggs (coturnix coturnix japonica) implemented with Arduino technology - Walter Francisco Game Cruz; Ligia Araceli Solis Lucas; Miguel Angel Lema Carrera; Veronica Cristina Andrade Yucailla (Universidad Ciencia y Tecnología, 2022)
Quail pups in St. Helena come from factory farms outside the province, making acquisition costs more expensive for the small producer. There are high-performance incubators for bird breeding, but their costs are not within the reach of an average poultry farmer. In this sense, to contribute to the developmentand increase the productivity of poultry breeding in small producers, Arduino technology was implemented to assemble incubators with low-cost materials for the average producer in the province. The techniques used in the research such as field notes, observation, and statistical tools yielded favorable results of 75% hatching and an efficiency of more than 83%. Observations by candling showed that the incubator system with Arduino is efficient in the formation of the chick. On the other hand, the investment costs for this equipment are attractive for the producer in the area.